2014
DOI: 10.1177/1757177414545390
|View full text |Cite
|
Sign up to set email alerts
|

Vomiting Larry: a simulated vomiting system for assessing environmental contamination from projectile vomiting related to norovirus infection

Abstract: Infectious diseases such as norovirus can induce emesis (vomiting), which can be of a projectile nature. Although studies have been carried out on transmission, prevalence and decontamination of such micro-organisms within various environments, little is known about the extent to which the surrounding environment is contaminated when an individual vomits. This is an important consideration for infection control purposes. The aim of this study was to develop a simulated vomiting system (Vomiting Larry) to be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 9 publications
1
13
1
Order By: Relevance
“…Vomiting is a well-characterized symptom during HuNoV infection. 32 However, vomiting is not a feature of CDI and no association with vomiting was seen in C. difficile -infected patients in our study. Interestingly, no association between vomiting and coinfection was observed.…”
Section: Discussioncontrasting
confidence: 73%
“…Vomiting is a well-characterized symptom during HuNoV infection. 32 However, vomiting is not a feature of CDI and no association with vomiting was seen in C. difficile -infected patients in our study. Interestingly, no association between vomiting and coinfection was observed.…”
Section: Discussioncontrasting
confidence: 73%
“…Simulated vomiting events have shown that a single vomiting event can contaminate a large area (7.8 m 2 ) and produce potentially infectious aerosols [ 29 , 30 ]. A recent study found that norovirus can survive in simulated emesis in suspension and on surfaces for up to 42 days [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [ 20 , 21 , 22 , 23 , 24 ] have assumed that the index patients’ vomiting episodes provided sufficient evidence of airborne transmission. Nevertheless, as Booth suggested experimentally [ 12 ], vomiting may contaminate a wide range of surfaces that are often difficult to clean sufficiently, thus increasing the likelihood of further transmission of surface contamination. Moreover, Marks et al [ 22 ] supported the possibility of airborne transmission because the time from exposure to illness decreased as the number of viral sources increased.…”
Section: Discussionmentioning
confidence: 99%
“…Although no evidence suggests that this virus is transmitted via the airborne route [ 9 ], the importance of this route has been suggested by several published reports [ 10 ]. In terms of biological plausibility, the potential of airborne transmission of norovirus exists [ 11 ], based on the findings of virus-containing aerosol droplets produced by vomiting [ 12 ] and toilet flushing [ 13 ], the detection of dispersed norovirus in the air [ 14 , 15 , 16 ], and the successful infection of mice via intranasal instillation [ 17 ]. In terms of outbreak investigations, a few studies [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ] have claimed to provide evidence for the airborne transmission.…”
Section: Introductionmentioning
confidence: 99%